an Analysis of Deixis in Avenger Infinity War Movie - Dessy Permata Sari; Zakrimal Zakrimal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to find out the types of deixis and the most dominant deixis that appeared in the Avengers Infinity War Movie. This study applied descriptive qualitative research. For collecting data, the researcher used non-participatory technique and observational method. The data in this study applied the theory from Levinson. The utterances of the speaker is used as the data in this study. The researcher found 168 data of deixis. The data were analyzed into person, temporal, place, discourse, and social deixis. The result showed that there are 87 person deixis, 31 temporal deixis, 14 place deixis, 21 discourse deixis, and 15 social deixis. Based on 168 data, the most dominant types of deixis is person deixis because most of all the character in the movie used person deixis. Keywords: Deixis, Linguistic, Pragmatic,